Haematological Changes of Critically ill Patients Admitted in CMH, Dhaka - Salsabil, Masuma Ahmed; Islam, Md Manirul; Ferdous, Jannatul; Hossain, Shameem Montasir (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Haematological status is an important parameter for the management of critically ill patients. Objective: To see the status of the haematological changes of critically ill patients admitted in CMH, Dhaka. Materials and Methods: This cross sectional study was conducted in the Department of Haematology of Armed Forces Institute of Pathology and Intensive Care Unit of Combined Military Hospital, Dhaka from March 2014 to September 2014 for a period of 6 months. All the patients who were admitted in the Intensive Care Unit of Combined Military Hospital, Dhaka at any age with either sex were included in this study. The complete blood count and coagulation parameters were considered and data sheet was prepared. Results: A total number of 862 samples were analyzed. Male female ratio was 1.8:1. Anaemia was found in 43.2% patients and 22.3% patients had Erythrocytosis. Normocytic Normochromic Anaemia was the most common morphological subtype of Anaemia. 13.8% patients had Leukopenia and 55.1% patients had Leukocytosis; 7.3% patients had Neutropenia and 49.0% patients had Neutrophilia. 10.0% patients had Eosinophilia. 26.3% patients had Lymphopenia and 14.7% patients had Lymphocytosis. 39.1% patients had Thombocytopenia and 20.3% patients had Thrombocytosis. MCV (Mean Corpuscular Volume) was below normal in 36.5% patients and was above normal in 16.8% patients. MCH (Mean Corpuscular Hemoglobin) was below normal among 49.7% patients and 11.1% patients above normal. MCHC (Mean Corpuscular Haemoglobin Content) was below normal level in 61.8% patients and 3.7% patients had above normal. Abnormal coagulation parameters that is prolonged PT, APTT and raised FDP was found in 36.3%, 18.6% and 35.8% patients. Conclusion: Critically ill patients were suffering from anaemia and thrombocytopenia with significant changes in other blood cells counts and coagulation parameters. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 63-67